Understanding the effects of technological advancement (Internet of Things) on value co-creation and firm performance - Ahmad Zaidi, Mohamad Faizal; Belal, H.M. (School of Technology Management and Logistics (STML), 2018)
This paper focuses on the effects of technological advancement in the relationships between value creation and firm performance. Specifically, this paper will explain how the concept of internet of things (IoT) can influence value co-creation and co-destruction towards firm performance from the perspective of resource-based view (RBV) and service-dominant (S-D) logic. This paper is motivated to discuss on the mentioned relationships due to four reasons. Firstly, although value co-creation has always been associated with positive implications on consumers (Terblanche, 2014); there are also some possible negative implications related to them (Grönroos, 2012). The same observation could also be happened to firm performance. For instance, increasing consumer participation will reduce firm controls on the outcome of the process. This situation would be ended up co-destructing the value through the very same consumer-firm interactions that are used in value co-creation (Terblanche, 2014). Therefore, the possibility of value co-destruction should not be overlooked (Plé & Cáceres, 2010) as it may as well affect the firm performance (Alexander, 2012). Despite of that, the numbers of studies focusing on both value co-creation and co-destruction in a single topic is still relatively low. Since the concept of value co-destruction is still in blur (Plé & Cáceres, 2010), the interrelationships between value co-creation and co-destruction need to be further explored.